Bayesian inference research in auditing: Some methodological suggestions* - ABDOLMOHAMMADI, MOHAMMAD J. (Contemporary Accounting Research, 1985)
Abstract. The Bayesian statistical inference model has been advocated by auditing researchers over the past two decades as a useful judgment aid to auditors. To quantify judgment, the Bayesian‐related audit research has completely relied on the elicitation techniques (ETs) and methodology used and recommended by Winkler (1967a). What have we learned from this literature? Are there any other promising ETs applicable to audit situations? What improvements can be made to the methodologies used in ET‐related audit research? This paper highlights the findings and methodologies of the existing literature, identifies promising ETs from related behavioral studies and draws some methodological suggestions for future research. Résumé. Des chercheurs dans le domaine de la vérification ont préconisé au cours des deux dernières décennies que le modèle d'inférence Baysien pouvait constituer une aide utile au jugement des vérificateurs. Pour quantifier le jugement, la recherche reliée au modèle Baysien s'est appuyée sur des techniques et une méthodologie utilisées et recommandées par Winkler (1967 a). Qu'a‐t‐on appris de ces recommandations? Peut‐on s'attendre à d'autres applications dans le domaine de la vérification? Quelles améliorations peuvent être apportées à la méthodologie? Cet article met en évidence les découvertes et la méthodologie sur le sujet, identifie les solutions prometteuses et présente certaines suggestions méthodologiques pour des recherches futures.